PHYSICOCHEMICAL PROPERTIES OF CARBON ADSORBENTS DERIVED FROM RENEWABLE BIOMASS - Ochilov, Akbarjon; Paygamova, Mahliyo; Khamzakhojayev, Asrorkhoja; Paygamov, Rakhimjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In recent years, the demand for environmentally friendly and economically efficient adsorbent materials has been steadily increasing. In this regard, the production of adsorbents from renewable resources—particularly agricultural and wood industry waste—has become a pressing issue. Poplar and willow trees are widely used in industrial applications, resulting in the generation of significant amounts of waste, such as stems, branches, and twigs. Instead of incinerating or discarding these residues, they can be recycled to obtain valuable adsorbent materials. This study investigates the thermal (TGA/DTA) and infrared (FTIR) properties of coal-based adsorbents prepared from the stem waste of poplar and willow trees. The wood residues were chemically activated with potassium hydroxide (KOH) at high temperatures. The resulting carbon materials were analyzed using thermogravimetric analysis (TGA) and differential thermal analysis (DTA) to determine their thermal stability, decomposition stages, and heat reactions. FTIR spectroscopy was employed to identify the presence of functional groups (O–H, C–H, C=C, C–O) and to evaluate their role in adsorption processes. The analysis revealed that the obtained carbon materials retained active functional groups capable of adsorbing pollutants. Such recycling of wood waste not only contributes to reducing environmental issues but is also economically advantageous. Therefore, these carbon adsorbents, derived from natural and low-cost raw materials, are considered promising candidates for applications in industrial and environmental fields.